New Directions in Rushdie Studies - Mendes, Ana Cristina (2017)
Released five years ago, Salman Rushdie’s memoir Joseph Anton (2012) serves as an important review of his life and oeuvre up to that point, (re)written from the author’s changing ideological positions and reflective of his attitudes one decade into the twenty-first century. Three years later, Rushdie published his most recent novel to date, Two Years Eight Months and Twenty-Eight Nights (2015). This special issue dedicated to exploring “New Directions in Rushdie Studies” sets out to survey the meaning and impact of this prolific author’s body of work up to the present moment, while highlighting some of the most innovative approaches in the field. Our aim is to offer new insights to the decades-long discussion over how Rushdie, as a writer, critic, and cultural icon, circumvents any categorization.